Mortgagee Remedies of Entry into Possession of Receivership: Ancient Equity Meets Modern Statute - Armstrong, Daniel (Victoria University of Wellington Law Review, 2000)
This article comprehensively catalogues and critiques the differences between the mortgagee remedies of entry into possession and receivership. In particular, the article looks at differences in how rights, duties, powers and liabilities of a mortgagor in possession as opposed to a receiver affect the choice of remedy. The author concludes that recent changes to the law in New Zealand have undermined the traditional advantages of receivership, and that equity is currently re-emphasising the rights of mortgagors.